2011
DOI: 10.3390/molecules16108209
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Catalyzed Environmentally Benign Deoxygenation of Epoxides to Alkenes

Abstract: We have developed a highly efficient and green catalytic deoxygenation of epoxides to alkenes using gold nanoparticles (NPs) supported on hydrotalcite [HT: Mg6Al2CO3(OH)16] (Au/HT) with alcohols, CO/H2O or H2 as the reducing reagent. Various epoxides were selectively converted to the corresponding alkenes. Among the novel metal NPs on HT, Au/HT was found to exhibit outstanding catalytic activity for the deoxygenation reaction. Moreover, Au/HT can be separated from the reaction mixture and reused with retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Notably, under the similar reaction conditions, the gold nanoparticles supported on hydrotalcite (Au/HT) gave more higher activity in this reaction than that of Ag/HT catalyst. 37 Slightly different from the alcohol-promoted deoxygenation of epoxides, Kaneda On the basis of previous findings and the silver-cerium dioxide coreshell nanocomposite (AgNPs@CeO 2 ) catalyst for reduction of nitroaromatic compounds, 28 Kaneda and coworkers 28 found that the AgNPs@CeO 2 exhibited unique reduction ability in the deoxygenation of epoxides to the corresponding alkenes (Scheme 9). Various epoxides including aromatic, aliphatic, and alicyclic epoxides were smoothly converted into the corresponding alkenes in excellent yields (94-98%) and selectivities (>99).…”
Section: Other Reductive Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, under the similar reaction conditions, the gold nanoparticles supported on hydrotalcite (Au/HT) gave more higher activity in this reaction than that of Ag/HT catalyst. 37 Slightly different from the alcohol-promoted deoxygenation of epoxides, Kaneda On the basis of previous findings and the silver-cerium dioxide coreshell nanocomposite (AgNPs@CeO 2 ) catalyst for reduction of nitroaromatic compounds, 28 Kaneda and coworkers 28 found that the AgNPs@CeO 2 exhibited unique reduction ability in the deoxygenation of epoxides to the corresponding alkenes (Scheme 9). Various epoxides including aromatic, aliphatic, and alicyclic epoxides were smoothly converted into the corresponding alkenes in excellent yields (94-98%) and selectivities (>99).…”
Section: Other Reductive Transformationsmentioning
confidence: 99%
“…Catalysis Science & Technology Minireview in this reaction than the Ag/HT catalyst. 37 Slightly different from the alcohol-promoted deoxygenation of epoxides, Kaneda et al also reported that deoxygenation of aromatic epoxides to alkenes could be efficiently catalyzed by Ag/HT using CO/H 2 O as a reductant. 38 On the basis of previous findings and the silver-cerium dioxide core-shell nanocomposite (AgNPs@CeO 2 ) catalyst for reduction of nitroaromatic compounds, 28 Kaneda and coworkers 28 found that AgNPs@CeO 2 exhibited a unique reduction ability in the deoxygenation of epoxides to the corresponding alkenes (Scheme 9).…”
Section: Other Reductive Transformationsmentioning
confidence: 99%
“…A basic site of the support abstracts H ? from hydroxyl group of 2-propanol followed by b-hydride transfer to Au 0 -NP thus forming [Au-H]hydride species [26,27]. The Au-hydride and H ?…”
Section: Resultsmentioning
confidence: 99%
“…[140] However, the development of synthetically useful reduction protocols occurred only in the last decade with the advent of nanoparticle catalysts. Hydrotalcite-supported silver [141] and gold, [142] as well as titania-supported gold nanoparticles, [143] are efficient promoters of the reduction of a variety of epoxides (Figure 11). Thanks to these contributions, the use of WGSR conditions represents one of the mildest and most efficient catalytic methods to date for this transformation.…”
Section: The Water-gas Shift Reaction In Organic Synthesismentioning
confidence: 99%